2014
DOI: 10.4028/www.scientific.net/amr.1024.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Applied Voltage on the Formation of Self-Organized Iron Oxide Nanoporous Film in Organic Electrolyte via Anodic Oxidation Process and their Photocurrent Performance

Abstract: Anodisation of iron foil was done to produce anodic film with nanoporous structure. The effect of anodic voltage on the morphology of the anodic oxide formed was investigated. Anodic film formed on iron foil anodised at 10 V is rather compact no obvious pores. Pores can be detected on oxide anodised at 30 V despite not very uniform. For foil anodised at 50 V, 1.8 µm thick anodic layer which consisted of uniform circular pores is observed. This film was then annealed at 450°C for 3 h in air as to induce crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Our result is higher than a photocurrent of ;0.26 mA/cm 2 at 0.6 V versus Ag/AgCl, reported by previous authors (for anodic nanoporous iron oxide annealed at 400°C for 30 min) 10 or a photocurrent of ;0.45 mA/cm 2 at 0.6 V versus Ag/AgCl for air-annealed sample. 13 This anodic nanoporous iron oxide was predominantly a-Fe 2 O 3 with a small amount of Fe 3 O 4 , and had a barrier layer thickness of ;800 nm. 10 The higher photocurrent for our sample may be attributed to the small thickness of the barrier layer for the nitrogen-annealed sample which is ;200 nm, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our result is higher than a photocurrent of ;0.26 mA/cm 2 at 0.6 V versus Ag/AgCl, reported by previous authors (for anodic nanoporous iron oxide annealed at 400°C for 30 min) 10 or a photocurrent of ;0.45 mA/cm 2 at 0.6 V versus Ag/AgCl for air-annealed sample. 13 This anodic nanoporous iron oxide was predominantly a-Fe 2 O 3 with a small amount of Fe 3 O 4 , and had a barrier layer thickness of ;800 nm. 10 The higher photocurrent for our sample may be attributed to the small thickness of the barrier layer for the nitrogen-annealed sample which is ;200 nm, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Lee et al reported on photocurrent of 0.25 mA/cm 2 at 0.39 V versus Ag/AgCl in 1 M KOH (100 mW/cm 2 , AM 1.5) for air-annealed nanoporous film with a thickness of ;0.2 lm. 15 Similarly in our previous report, a photocurrent of 0.33 mA/cm 2 at 0.39 V versus Ag/AgCl was reported utilizing an anodic nanoporous photoanode with a thickness of ;1.8 lm annealed in air at 450°C for 3 h. 13 The relatively low photocurrent values may be attributed to the above mentioned problems: oxidation of iron during annealing, thickening of barrier layer and Fe 3 O 4 and/or FeO formation. In this present work, we investigated on the formation of the nanoporous iron oxide and on the effect of nitrogen annealing to the properties of the nanoporous oxide and on the photocurrent response when the oxide film was illuminated.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation